Small and overlooked: Phylogeny of the genus Trigonodactylus (Squamata: Gekkonidae), with the first record of Trigonodactylus arabicus from Jordan - Pola, Lukáš; Hejduk, Vojtěch; Zíka, Aleš; Winkelhöfer, Tomáš; Šmíd, Jiří; Carranza, Salvador; Shobrak, Mohammed; Abu Baker, Mohammad; Amr, Zuhair Sami (Saudi journal of biological sciences, 2021)
Geckos of the genus Trigonodactylus are widely distributed in the sand deserts of the Arabian Peninsula. Three species of this genus are currently recognized, with a fourth one, Stenodactylus pulcher, which placement within Trigonodactylus has been tentatively suggested, but not yet confirmed. We present a phylogenetic analysis of the genus Trigonodactylus with new specimens collected in central Saudi Arabia and southern Jordan. New genetic data has been generated from three mitochondrial markers to investigate the phylogenetic relationships of all species of the genus and to assess the putative generic assignment of S. pulcher. Our results confirm that S. pulcher indeed belongs within Trigonodactylus, branching as a sister lineage to all other species of the genus. The new samples cluster within Trigonodactylus arabicus, thus confirming the genetic homogeneity of the species across its large and seemingly inhospitable range. The new specimen collected in southern Jordan represents the first record for the country and a considerable range extension to the northwest from all previously reported localities. Our findings and discovery of a new species for Jordan highlight the need of more field surveys to be carried out in the underexplored parts of Jordan and northern Saudi Arabia, as these places still hold a potential for new discoveries and are crucial for understating the biogeography of the Arabian herpetofauna.
Keywords: Mitochondrial DNA; Stenodactylus; Middle East; Palearctic naked-toed geckos; Range extension